Pengaruh Kedisiplinan, Lingkungan Kerja, dan Motivasi terhadap Kinerja Pegawai pada Kantor Pelayanan Pajak Pratama Bandung Tegallega - Evi Wahyusari Hernaningsih; Sunardi Sembiring Brahmana (Jurnal Syntax Admiration, 2024)
This study aims to find out and analyze how much the influence of discipline has a significant effect on employee performance at the Bandung Tegallega Primary Tax Service Office. The population of this study is 75 employees of the Bandung Tegallega Primary Tax Service Office. To meet the number of samples, the sampling method in the field uses random sampling techniques. The researcher determined a sample of 75 respondents who were employees of the Bandung Pratama Tax Service Office. As a result, the work motivation of employees is still in the sufficient category, so it needs to be improved so that the performance of employees who are also in the sufficient category can increase. Discipline and Work Environment are classified as good and need to be maintained. Discipline, Work Environment, and Work Motivation each have a significant positive effect on Employee Performance, with Discipline and Work Environment making a major contribution to improving Performance. Overall, these three variables affect Employee Performance by 82%, while the remaining 18% is influenced by other factors that are not studied.